Does Discount Matter in Indonesia e-Wallet Race? A Generation Z e-Wallet Preferences During Pandemics - Arum Prasasti; Fatwah Inna Aulisaina; Muhamad Arif Rahman Hakim (The Winners, 2021)
The research aimed to examine the intention of Generation Z when using e-wallet for payments and the influence of  discounts towards using e-wallet in the time of pandemics. The research applied a qualitative method with total data of  22 students, collected using in-depth interviews through WhatsApp free call. The result shows that discount gives an  impact on Generation Z in choosing the e-wallet, but a long-term loyalty is not guaranteed. The finding demonstrates that there are other influential factors for Generation Z to choose e-wallet, namely ease of use, interrelated apps with the e-wallet, the security system, and cashless society. The limitations of the research lie in the relatively small numbers of  respondents. Due to pandemics with physical distancing requirements, the research only carries out on data collected  from 22 students from Economics Faculty in the State University of Malang, Indonesia. However, the research provides an  insightful analysis for digital payments industry as a reference. It is expected that fellow researchers and academicians  use the research as a fundamental to further investigate digital payments, especially amongst Generation Z in Indonesia  or other parts of the world.